Enzyme Immobilization Based on Metal-Organic Frameworks and Its Biosensing Applications - Sun, Feilu (Transactions on Materials, Biotechnology and Life Sciences, 2024)
Many studies have shown that metal-organic frameworks (MOFs) that immobilized enzymes have broad application prospects. As highly efficient biological catalase, enzymes are easily inactivated under some special conditions, which becomes a major obstacle to industrial catalysis and hinders their wide application. However, when the enzyme is immobilized, its disadvantages such as instability and low recyclability are improved, resulting in higher catalytic efficiency and cost savings. The use of flexible, stable, and efficient MOFs as platforms for immobilized enzymes is considered to be a better scheme. In this research, four methods of enzyme solidification in MOFs, namely, in situ encapsulation, surface attachment, covalent conjugation and entrapment, are introduced, including their principles, applications, main advantages and disadvantages. At the same time, the applications of enzyme-multiple organ function (enzyme-MOFs) biosensors in the fields of environment, food and medicine are reviewed, including environmental contaminant detection, contaminant degradation, food safety detection, glucose detection and drug transportation. Finally, some current technical problems are briefly listed, and the technological development in the field of enzyme-MOFs biosensor is prospected.